Multiculturalism in Liberal and Islamic Perspectives: A Philosophical Review - Moeis, Isnarmi (EDUCARE, 2009)
ABSTRACT: It is used to discuss multiculturalism comes from liberal philosophy since the latest improvement of the multiculturalism ideas occur in liberalism society like American and European. To understand the meaning of multiculturalism, however, culture is viewed as a dynamic process of human adaptation toward their historical journey as the way to defense their life through a sympathetic involvement in understanding and responding the world. The connection of multiculturalism to liberalism ideas shows that multiculturalism is a further improvement of political philosophy of liberalism, or it may be also inferred that multiculturalism is an antithesis toward liberal political theory itself. However, the ideas of multiculturalism also develop in Islamic tradition. The basic multiculturalism concept in Islam can be traced in daily life of plural society during the Medina government under the Prophet Muhammad SAW (peace be upon him)âs authority and furthermore continued by the next generation. The distinctions of multiculturalism concepts between liberal and Islamic perspectives can be an interesting topic to discuss as an effort to enrich multiculturalism understanding that now becomes a real challenging idea in this globalization era.KEY WORDS: multiculturalism, tolerance, equality, cultural diversity, and liberalism and Islamic perspectives.About the Author: Dr. Isnarmi Moeis is a Lecturer at the Department of Civic Education, Faculty of Social Sciences UNP (State University of Padang), Jalan Prof. Dr. Hamka Kampus UNP Air Tawar, Padang 25131, West Sumatera, Indonesia. She can be reached at: isnarmi213@yahoo.comHow to cite this article? Moeis, Isnarmi. (2009). âMulticulturalism in Liberal and Islamic Perspectives: A Philosophical Reviewâ in EDUCARE: International Journal for Educational Studies, Vol.2(1) August, pp.17-24. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 5, 2009); Revised (July 5, 2009); and Published (August 17, 2009).